Thrombin Generation Induced by the Intrinsic or Extrinsic Coagulation Pathway is Accelerated by Streptokinase, Independently of Plasminogen - Brommer, E J P; Meijer, P (Thrombosis and Haemostasis, 1993)
Thrombolytic therapy paradoxically induces the formation of fibrinopeptide A, fibrin degradation products and thrombin-antithrombin complexes, indicating thrombin generation. Part of the mechanism of this thrombin generation under the influence of thrombolytic agents was unraveled in this study.We measured thrombin with a chromogenic substrate at several time intervals after recalcification of citrated plasma which had been preincubated with urokinase, streptokinase, recombinant tissue plasminogen activator (rt-PA) or recombinant singlechain urokinase-type plasminogen activator (rscu-PA). Thrombin generation induced by the addition of thromboplastin together with calcium (extrinsic pathway) was greatly accelerated in the presence of streptokinase (from about 7 to 2 min), and to a lesser extent in the presence of urokinase, rt-PA or rscu-PA. Similar effects were seen after the addition of calcium to the plasma containing the thrombolytic agent and preincubated with partial thromboplastin (intrinsic pathway). Hirudin quenched the conversion of the chromogenic substrate completely, confirming that thrombin was the active enzyme. Aprotinine did not affect the results, and the effect of streptokinase was also observed in plasminogen-depleted plasma. We conclude that streptokinase, and to a lesser extent other thrombolytic agents, activate the prothrombinase complex directly or indirectly through a calcium-dependent mechanism, independently of plasminogen, with a resulting acceleration of thrombin generation.